DEVELOPMENT OF EDUCATIONAL SOFTWARE FOR THE DESIGN OF REINFORCED CONCRETE BEAMS AND SLABS - Neto, Gabriel Antonio; Florian, Fabiana; Quaresma, José Eduardo (Revista Interface Tecnológica, 2020)
The main objective of this work is to present free software for microcomputers that is easy to understand and friendly interface, in order to numerically solve the problem of dimensioning beams and slabs, from pre-dimensioning to reinforcement, longitudinal and stirrups, showing graphically and numerically the bending and cutting moment in beams based on the Brazilian standard NBR 6118-2014. This application, called Orion, was developed with the objective of facilitating students' understanding of structural calculations in reinforced concrete, being used only for academic purposes, showing the results obtained in a simple and quick way. The concept of free software is not widespread in Brazil, when it comes to free software for civil engineering there is great difficulty in finding good programs, after all free software is a computer program distributed under conditions that allows users to study it, modify it it and distribute it. The software is considered free if it provides the user with final control over the source code of the program, allowing its modification and subsequent distribution. For the development of Orion, the JAVA programming language was used in order to maximize its reach by making it multiplatform and reaching the largest number of people.
Keywords: Reinforced concrete; Beam; Slab; Cutting moment; Bending moment